Exchange Behaviour of Amorphous AlPO towards Cu Ions - Muhammad Javid; Syed Mustafa; Muhammad Iqbal Zaman; Rana Gul (Adsorption Science & Technology)
Sorption studies of Cu 2+ ions onto AlPO 4 were carried out as a function of pH (3–5) and temperature (303–323 K). The extent of sorption was found to increase with an increase in Cu 2+ ion concentration, pH and the temperature of the system. The Kurbatov equation along with a new equation based on the law of mass action were found applicable to the sorption data. The sorption mechanism was found to consist of an exchange between the H + ions from the exchanger and Cu 2+ ions from the aqueous solution. The thermodynamic parameters evaluated showed that the process was endothermic and non-spontaneous in nature. FT-IR spectroscopy was also employed to evaluate the mechanism of Cu 2+ ion sorption.